Impacts of climate change on livelihood of the fishersˊ at the Meghna, Laukhati and Galachipa river in Bangladesh - Rahaman, Md Jiaur; Hossain, Md Saddam; Rahman, Mohammad Matiur; Hossain, Zakir (Asian Journal of Medical and Biological Research, 2020)
Climate change is a global threat to the world especially for Bangladesh, due to its geographical location. The present study was carried out to the impacts of climate change on livelihood of the fishers at the Meghna, Laukhati and Galachipa river in Bangladesh. The study was assessing the effects of climate change on fishersˊ community in the Meghna, Laukhati and Galachipa rivers near Chandpur and Patuakhali districts. The data on fishersˊ livelihood were collected by using a well-developed questionnaire from the selected areas. The average temperature was recorded as 30.5±0.90°C, 27.1±1.05°C and 27.4±0.60°C and the dissolved oxygen was as 6.37±1.11 mg/L, 5.63±0.33 mg/L and 6.33±0.51 mg/L in the Meghna, Laukhati and Galachipa rivers, respectively. The pH was as 8.3±0.59, 8.03±0.50 and 7.8±0.50 and the salinity was as 0.10±0.10, 0.23±0.13 and 1.2±0.15 ppt in the Meghna, Galachipa and Laukhati rivers, respectively. In the present study, it was found that most of the fishers were belonged to the age groups of 41 to 60 years (45%), represented by 75% muslim and joint family type (61%) was the predominant among the fishers. The highest annual income of fishers was found 20,080 and 24,000 BDT per year at Chandpur and Patuakhali districts, respectively. There has not been conducted much empirical research about the impacts of climate change in the present research areas. Therefore, Government and NGOs should take proper steps by taking various need based projects and providing some sorts of management policy to rescue the vulnerable communities from climate change impacts. Asian J. Med. Biol. Res. March 2020, 6(1): 81-92